FACTORS AFFECTING REPRODUCTIVE TRAITS IN SEVERAL BREEDS OF DAIRY CATTLE IN IRAQ - & Hadad, Hermiz (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study aimed to investigate the factors affecting reproductive traits using records collected during two calving seasons (2016-2017) and (2017-2018) from three herds of dairy cattle bred at Erbil-Iraq, and includes 323 lactation period (LP), 159 age at first calving (AFC) and 159 calving interval (CI). GLM within SAS used to diagnose the significance effects of the available factors affecting the studied traits. Repeatability of LP also estimated. Overall mean of LP, AFC and CI for the three breeds in all herds were 300.14 days, 27.709 months, and 360.26 days respectively. Simmental recorded significantly (p<0.01) higher LP (302.95 days) comparing with Friesian (296.81 days) and Bokane (293.24 days). Differences in LP due to the herd were significant (p<0.01). LP decline significantly (p<0.01) from 306.05 days in the 1st parity to 290.22 days in the 4th parity. Effects of year and season of calving on LP were not significant. Cows calved females had significantly longer LP (299.39 days) than cows calved males (295.95 days). Regression of LP on AFC (0.207 day/mo.) was not significant, while regressions on body weight of cow at calving (0.088 day/kg) and on birth weight of their calfs (1.661 day/kg) were significant. Repeatability estimate for LP was 0.55. Differences in AFC due to the breed were highly significant, while the effect of herd, year and season of birth were not significant. Regression of AFC on their body weight at calving was not significant (-0.01 day/kg). Differences among the breeds, herds and parities in their CI were not significant. Cows calved in winter and spring recorded significantly shorter CI as compared with those calved in summer and autumn. Regression coefficient of CI on AFC (0.692 day/mo.) was not significant, while the regression on body weight of cow at calving (0.151 day/kg) was highly significant.